Strategi Perpustakaan dalam Mengatasi Keterbatasan Anggaran untuk Memenuhi Minat Baca Pemustaka pada Koleksi Bestseller Indonesia di Perpustakaan Kota Mataram - Harnilansari; Lilian Apriliati; Nurlailah; Nurul Fajrin; M. Ananda Aryadi; Iskandar (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2026)
This study is motivated by the high reading interest of users in Indonesian bestseller collections at the Mataram City Library, which has not been fully matched by the availability of collections due to budget limitations and efficient procurement processes that require considerable time. This study aims to analyze the strategies implemented by the library in overcoming budget constraints to meet user needs for bestseller collections. The research method used is qualitative with a descriptive approach. Data collection techniques include observation, interviews, and documentation. The results show that bestseller collections have a high borrowing rate because they are relevant to daily life, easy to understand, and follow current reading trends in society. The strategies implemented include user-demand-based collection procurement, utilization of book donations and grants, collaboration with various parties, optimization of digital services such as e-books and iPusnas, and the use of social media and surveys to gather user suggestions. These strategies are considered fairly effective in helping the library meet user information needs despite budget constraints. In conclusion, Mataram City Library has implemented adaptive and innovative strategies in managing bestseller collections; however, stronger budget support and broader cooperation are still needed to optimize services and collection development.